A Comparative Analysis of Attitudinal Meaning in the Representation of Dutch and Indonesian Officials in Max Havelaar’s Indonesian Translated Novel - Putri, Hana Andari Eka; Ningsih, Harni Kartika; Sutanarihesti, Triaswarin (Riviera Publishing, 2025)
Max Havelaar is a novel written by the Dutch author Eduard Douwes Dekker, widely regarded as an illustration of the author’s opposition to the exploitation and oppression perpetrated by the Dutch colonial government and local officials against the natives in the Dutch-East Indies. This study aims to conduct a comparative analysis of attitudinal meaning, examining the sentiments of Dutch and Indonesian officials as reflected in the Indonesian translation of Max Havelaar. The 2014 translated edition published by Qanita was selected for analysis, with data drawn specifically from chapters V to XX. The Appraisal framework was employed to reveal patterns of evaluative meaning manifested through the portrayal of Dutch and Indonesian officials. This framework centers on the ATTITUDE system, investigating how the resources of AFFECT, APPRECIATION, and JUDGMENT are utilized to construct evaluative stances towards both groups of officials, in alignment with the field of Comparative Analysis of Attitudinal Meaning. Findings indicate that both Dutch colonial and Indonesian officials are predominantly evaluated through negative attitudinal resources, with frequent deployment of unfavorable assessments that serve to critique the pervasive injustices of colonial rule. Notably, the Indonesian officials are depicted in a dual characterization: they are simultaneously portrayed as victims of colonial oppression and as complicit contributors to the mechanisms of that very oppression. This dual appraisal foregrounds the complexity of colonial dynamics as represented in the novel and highlights the value of attitudinal analysis in uncovering nuanced ideological positions.